An Allee effect reduces the invasive potential of Tilletia indica - Bowden, Robert L.; Garrett, Karen A. (My University, 2007)
The Karnal bunt pathogen, Tilletia indica, is heterothallic and depends on encounters on wheat spikes between airborne secondary sporidia of different mating types for successful infection and reproduction. This life history characteristic results in reduced reproductive success for lower population densities. Such destabilizing density dependence at low population levels has been described for a range of animals and plants and is often termed an Allee effect. Our objective was to characterize how the Allee effect might reduce the invasive potential of this economically important pathogen. We developed a simple population model of T. indica that incorporates an Allee effect by calculating the probability of infection for different numbers of secondary sporidia in the infection court. An Allee effect is predicted to be important at the frontier of an invasion, for establishment of new foci by a small population of teliospores, and when the environment is nonconducive for the production of secondary sporidia. Using estimated model parameter values, we demonstrated a theoretical threshold population size below which populations of T. indica were predicted to decline rather than increase. This threshold will vary from season to season as a function of weather variables and their effect on the reproductive potential of T. indica. Deployment of partial resistance or use of fungicides may be more useful if they push population levels below this threshold.
Citation: Garrett, K. A., Bowden, R. L. (2002). An Allee Effect Reduces the Invasive Potential of Tilletia indica. Phytopathology, 92(11), 1152-1129. https://doi.org/10.1094/PHYTO.2002.92.11.1152
Keywords: Allee effect; Tilletia indica; Minimum viable population; Partial bunt; Spore bank; Threshold criteria; Depensation; Invasive species